ENHANCING INVERTER PLANT HOUSE IN SOLAR POWER MODIFIED BASED ON SINUS WAVE - Solly Aryza; Hamdani Hamdani (Jurnal Elektro dan Telkomunikasi, 2020)
This research aims to produce an inverter device which is implemented in a solar power plant for homes. In solar power generation systems, an inverter is a device that functions to change the direct cureent into alternating current. In this study, an inverter device was designed to produce an output of electrical quantities in accordance with the needs of residential electrical equipment. The design shows the important role of the microcontroller as a control unit and IGBT component as a component of power electronics. the test results show that the inverter has been able to produce an output with a voltage of 220 V and a frequency of about 50 Hz with a sine wave output, but there are still defective wave. Until this article is prepared improvements are still being made.